2014
DOI: 10.1158/1078-0432.ccr-13-2497
|View full text |Cite
|
Sign up to set email alerts
|

microRNAome Expression in Chronic Lymphocytic Leukemia: Comparison with Normal B-cell Subsets and Correlations with Prognostic and Clinical Parameters

Abstract: Purpose: Despite its indolent nature, chronic lymphocytic leukemia (CLL) remains an incurable disease. To establish the potential pathogenic role of miRNAs, the identification of deregulated miRNAs in CLL is crucial.Experimental Design: We analyzed the expression of 723 mature miRNAs in 217 early-stage CLL cases and in various different normal B-cell subpopulations from tonsils and peripheral blood.Results: Our analyses indicated that CLL cells exhibited a miRNA expression pattern that was most similar to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 53 publications
2
73
0
Order By: Relevance
“…17,19,50,51 Increased miR-34a levels have been noted in several CLL studies. 26,29,52,53 Inhibition of miR-34a by antisense RNA has been shown to sensitize lymphoma cells to apoptosis. 54 We found that levels of miR-34a were 87-fold higher in circulating CLL cells in comparison to normal circulating B-cells; and miR-34a was significantly higher in CLL cells in the lymph node than that in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,19,50,51 Increased miR-34a levels have been noted in several CLL studies. 26,29,52,53 Inhibition of miR-34a by antisense RNA has been shown to sensitize lymphoma cells to apoptosis. 54 We found that levels of miR-34a were 87-fold higher in circulating CLL cells in comparison to normal circulating B-cells; and miR-34a was significantly higher in CLL cells in the lymph node than that in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 miR-34a and miR-146b were both previously reported to target SMAD4; 39-42 and miR-34 was reported to target HDAC1 43,44 in solid tumor cell lines resulting in inhibition of both mRNA and protein expression. In order to confirm inhibition of mRNA transcripts and protein expression regulated by miR-34a and miR146b in B-cell leukemia cell lines, premiR oligonucleotides were transfected into SP53 and MEC1 cells.…”
Section: Ibrutinib Responsive Mirnas Target Multiple Tumor Suppressormentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of miR-15/16 in CLL was reviewed in detail by Pekarsky and Croce [17]. Many studies addressed miRNA expression in lymphocytes of CLL patients and tested its correlation with clinical and prognostic parameters [3841]. New possibilities have opened with the discovery of circulating miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,4 MiRNAs are dysregulated in almost all solid and hematological malignancies, and specific signatures allow the characterization of poorly differentiated tumors 5 as well as harbor relevant clinical implications. 6,7,8,9 MiRNAs, which are upregulated in cancer cells and contribute to carcinogenesis by inhibiting tumor suppressor genes, are considered oncogenic miRNAs (OncomiRs), 10 while downregulated miRNAs, that normally prevent cancer development by inhibiting the expression of proto-oncogenes, are known as tumor suppressor miRNAs. 11 Silencing Oncomirs with miRNA inhibitors or replacing tumor suppressor miRNAs with synthetic miRNA mimics is demonstrating a valuable experimental strategy for the treatment of solid and hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%